THE ROLE OF THE ISLAMIC FIGURE IN REGIONAL DEVELOPMENT OF BANGKALAN REGENCY - Hapsari, Mega Tunjung; Himawan, Mohammad Hilmi (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
The present research aims to analyse and describe the role of the Islamic figure as the main actor of the regional development as seen from a right governance perspective in Bangkalan Regency, Madura. This research is classified as descriptive research with a qualitative approach. This research employs a descriptive qualitative approach by implementing the Interactive model of Miles, Huberman, and Saldana as the data analysis through data condensation, data display, and conclusion drawing and verifying. The results show that the Islamic figure plays a significant role in making the regional development of the Bangkalan Regency successful, such as in decision making, infrastructure development, and social development. This research has implications for scientific progress in the field of Islamic studies, which is the results of this study prove that the leadership style with Islamic values can make governance practices better and more dignified. The role of the Islamic figure also leads to the government bureaucracy change through the implementation of ethical governance principles such as strategic vision, participation, accountability, effectiveness, and efficiency